CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon


Question

Equation of the line passing through (–1, 1) and perpendicular to the line 2x + 3y + 4 = 0, is
  1. 2(y – 1) = x + 1
  2. 3(y –1)= –2(x + 1)
  3. y – 1 = 2(x + 1)
  4. 3(y – 1) = x + 1


Solution

The correct option is A 2(y – 1) = x + 1
The gradient of line 2x + 3y + 4 = 0 is 23. Now the equation of line passing through (-1,1) is y-1=m(x+1), but m=123=32. Therefore the required equation is 2(y – 1) = x + 1.

flag
 Suggest corrections
thumbs-up
 
0 Upvotes


Similar questions
QuestionImage
QuestionImage
View More...



footer-image